Influence Implementation Human Resource Management Against Power Sell Madura Batik Msmes Products - Fawaid, Akh; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2024)
The purpose of this study is to evaluate how human resource management (HR) adoption affects Madura Batik MSME product sales. Six out of the eighteen batik centres in Pamekasan were the sites of in-depth interviews with owners, managers, and staff of Batik MSMEs in Madura, using a qualitative descriptive research methodology. Thirty people made up the study's subjects: six batik MSMEs' owners, eight managers, and fifteen employees. To ascertain the successes of business development and assess the company, a SWOT analysis is required. The analysis's findings demonstrate that putting in place efficient HR management practices—like employee empowerment and training—helps firms adapt to changing market conditions and boosts output and quality of work. The effect is that the product's selling power will rise with optimal HR management implementation and vice versa.